Principles of accounting - Holmes, G. A. (Great Britain : Butler & Tanner Ltd., 1960)
In the preparation of this edition the opportunity has been taken to extend the text to cover the revised requirements of the professional examining bodies and to illustrate the effect of the provisions of the companies Act 1984, in relation to modern accounting practice. The latest recommendations of the Institute of chartered Accounting have been written into the text and are incorporated in Appendix II.
Includes indexes.
hza 01/02/2019
Loans
Keywords: Accounting; Accounting principles